Oral alterations associated to gastroesophageal reflux disease - Yulisa Otero Baxter; Carlos Jesús Llapur Almaguer; Maritza Osorio Nuñez; Edelis Raimundo Padrón (Editorial Ciencias Médicas, 2020)
Introduction: Gastroesophageal reflux disease is a functional multifactorial disorder of the upper gastrointestinal tract. Oral alterations are considered to be extraesophageal manifestations of this disease. Objective: Determine the oral alterations found in patients with gastroesophageal reflux disease. Methods: An observational descriptive study was conducted of 37 patients diagnosed with gastroesophageal reflux disease. The variables analyzed were age, sex, presence of alteration, signs and symptoms, and location. A database was developed with the information recorded, and absolute frequencies and percentages were estimated. Results: Of the patients studied, 48.6% had some sort of oral alteration, such as a burning sensation (40.5%) and erythema (35.1%). The regions affected included the soft palate / uvula (72.2%) and the tongue (61.1%). Conclusions: Almost half of the patients affected by gastroesophageal reflux had some sort of oral manifestation, the most common of which were a burning sensation, erythema, a dry mouth sensation and ulcerations. The most common locations were the soft palate / uvula and the tongue.